Implementation of Blue Ocean Strategy in Facing Business Competition: A Startup Case Study of Lapangbola.Com - Hermawan, Adam; Hurriyati, Ratih; Hendrayati, Heny; Sultan, Mokh Adib (Universitas Muhammadiyah Yogyakarta, 2024)
Research aims: This study discusses the specific blue ocean strategy employed by lapangbola.com to emerge successful in the business competition.Design/Methodology/Approach: This study employed a descriptive qualitative methodology, utilizing interviews with relevant individuals (Operations and Marketing managers) from lapangbola.com. The analysis was conducted using the Blue Ocean Strategy, employing a strategy canvas, a four-step framework, and a six-step framework for data gathering.Research findings: A business competition strategy employs a blue ocean strategy approach that originates from business innovation, encompassing product development, operational enhancements, and the utilization of efficient digital marketing channels.Theoretical Contribution/Originality: This research serves as valuable information for decision-makers, particularly in startup firms, seeking to enhance their business growth by adopting a blue ocean strategy approach. The successful implementation of this technique by lapangbola.com, a startup business in the sports industry, further exemplifies its effectiveness.Practitioners/Policy Implications: Startup companies or businesses in the digital industry might employ a blue ocean strategy, characterized by a rigorous, flexible, and inventive approach, to analyze the market and formulate an effective formula for company development.Research Limitations/Implications: The limitations of this research are found in the secondary data (literature studies) used, this is because not many businesses have consciously implemented blue ocean strategy simultaneously using canvas strategies, 4-step frameworks and 6-step frameworks. More in-depth analysis is needed on the implementation of the blue ocean business strategy that will be carried out at each startup.